PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PELAKU TINDAK PIDANA CYBERBULLYING (Studi Putusan Nomor 46/pid.Sus/2019/PN Lhokseumawe) - Dewiana, Dewiana; Hasbi, Yusrizal; Saputra, Ferdy (Fakultas Hukum Universitas Malikussaleh, 2024)
The increase in internet users makes cyberbullying a threat to various groups. Cyberbullying behavior may increase due to the anonymity afforded by online interactions. The cyber world has a significant impact on various aspects of people's lives, but this influence is not always positive and can have negative impacts. Currently, cyber crime provisions in Indonesia are mainly regulated in the ITE Law which focuses more on electronic transactions than cyber crime. The lack of specific regulations regarding Cyberbullying in the ITE Law highlights the need for the government to address this problem and provide stronger protection for victims by defining Cyberbullying and taking firm action against violators.